The Global Economic and Financial Impact of an Avian Flu Pandemic and the Role of the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper, prepared by a working group of IMF staff, provides a preliminary assessment of the risks and potential impact to the global economy and financial system from a possible avian flu pandemic, discusses the IMF's role in helping member countries prepare their economic and financial systems for such a pandemic, and summarizes common elements of business continuity planning in the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet